Caregiver Variables on Preschoolers’ Classroom Participation in Public Early Childhood Centres of Rivers East Senatorial District of Rivers State - Princewill Okechukwu , Ejekwu; Juliet, Oriaku (International Journal on Integrated Education, 2025)
The study looked into how carer characteristics affected preschoolers' involvement in class at public early development facilities in Rivers State's East Senatorial District. The research design used in the study was a descriptive survey. Six research questions and six hypotheses that were assessed at the.05 alpha levels of significance served as the study's compass. 717 carers made up the study's population. 287 carers made up the study's sample. Both basic random sampling and stratified sampling were used to choose the sample. The researcher's validated "Carers' Variables and Classroom Participation of Preschoolers Questionnaire (CVCPPQ)" served as the data gathering tool. The reliability coefficient of the instrument was 0.68. The study's results, which were obtained using the statistical tool Analysis of Variance (ANOVA), indicate that the qualifications of carers have a significant impact on the classroom participation of preschoolers in public early childhood centres in Rivers East Senatorial District of Rivers State; the teaching experience of carers has a significant impact on the classroom participation of preschoolers in public early childhood centres in Rivers East Senatorial District of Rivers State; and the gender of carers has a significant impact on the classroom participation of preschoolers in public early childhood centres in Rivers State.